Impact characteristics of the ball and racket during play at the Wimbledon qualifying tournament - Choppin, S.; Goodwill, S.; Haake, S. (Sports Engineering, 2011)
There has been little three-dimensional (3D) analysis of the interaction of a tennis ball and racket during realistic play conditions. This paper is a descriptive study of elite players in practice conditions. The method used records racket and ball movement in 3D, intrudes minimally into the player`s environment and has a high level of portability. Testing was performed using two Phantom V4.2 high speed video cameras operating at 1,000 frames per second. Racket movement was tracked using five reflective markers attached to the player`s racket and the ball was tracked as a single point. The method allowed accurate measurement of ball and racket speeds, impact positions, and angular velocities of the racket in three-dimensions. It was used at the 2006 Wimbledon qualifying tournament in practice conditions to record 106 shots from 16 internationally ranked players. The results obtained showed that all players aim to hit the node point on the racket face in a standard forehand drive. The average post-impact ball velocity of male players was 9.4% greater than that of female players at 33.9 m s-1, post-impact ball spin was 22.3% higher at 1,480 rpm. These results could be used to confirm previous research into player movement and impact, or as a basis for future investigation into the interaction between the ball, racket and player.